NOISE MAPPING IN THE TURBINE AREA AT PT POMI - Ismara Nareswari; Ahmad Imaduddin; Y. Denny Ardyanto Wahyudiono (Journal of Vocational Health Studies, 2023)
Background: One of the problems faced by industrial companies that use large machines and work equipment is noise. Steam power plant companies will certainly face noise problems in their work areas. PT. Paiton Operation and Maintenance Indonesia is one of the private power generation companies in East Java which manages three units of PLTU (Steam-Electric Power Plant) which in the process operates using a turbo generator. In addition, this company uses machines and equipment that produce noise that can potentially interfere with the health of the workers. Purpose: To map the noise with Golden Surfer software and to analyze the control efforts that had been carried out. Method: This research used an observational method and the analysis was done using Golden Surfer software. Result: The results of this study indicated that in general the noise that occurred in the turbine area exceeded the threshold value which was >85 dB. Furthermore, the results of the mapping showed the distribution pattern of noise levels that occurred in the turbine area starting from the first floor to the fifth floor. Noise control efforts were also carried out by the company, including noise measurements, scheduled preventive maintenance for machine repairs, safety sign, audiometric checks, work procedures, and PPE. Conclusion: In addition to this noise mapping, noise control efforts that have been carried out by the company will reduce the risk of health problems for workers. Thus, noise mapping can be used as a basic reference for companies to be able to determine additional noise control as an effort to prevent and control noise.